Autosomal recessive otospondylo-mega-epiphyseal dysplasia: Comprehensive clinical review of a pediatric cohort - ELÇİOĞLU, HURİYE NURSEL (My University, 2023)
Autosomal recessive otospondylo-mega-epiphyseal dysplasia (OSMEDB) is characterized by short stature with short limbs, dysmorphic facial features, and hearing loss, which is caused by biallelic, loss-of-function, variants in the COL11A2 gene. Geno-phenotypic data from the medical records of eight affected individuals from five unrelated families was abstracted, recorded in an Excel spreadsheet and analyzed using simple frequency analysis. Either short femora or short extremities with or without other ultrasonographic abnormalities were demonstrated in five patients antenatally. The mean height was -2.29 SDS. Pectus deformity, including either chest asymmetry or pectus excavatum, was present in five patients. Bilateral hearing loss was verified in all patients. Severe speech delay and learning disabilities were present in two patients whose deafness was realized after the age of 12 months. Four novel loss-of-function variants in COL11A2 were found in this cohort. We present novel geno-phenotypic findings in a pediatric cohort with OSMEDB. The age of manifestation of short stature was variable, ranging from birth to middle childhood, and the severity of short stature varied even within the same family. Hearing loss may not be evident in the neonatal period and manifest later in OSMEDB. Intermittent hearing tests should be performed for early intervention of neurolinguistic delay and learning disabilities.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Tıbbi Genetik; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Anatomi; Biyokimya; Temel Bilimler; Medicine; Internal Medicine Sciences; Child Health and Diseases; Medical Genetics; Surgery Medicine Sciences; Pathology; Life Sciences; Molecular Biology and Genetics; Health Sciences; Fundamental Medical Sciences; Human Anatomy; Biochemistry; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; PEDİATRİ; PATOLOJİ; ANATOMİ VE MORFOLOJİ; GENETİK VE KALITIM; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; PEDIATRICS; PATHOLOGY; ANATOMY & MORPHOLOGY; GENETICS & HEREDITY; Pediatri, Perinatoloji ve Çocuk Sağlığı; Patoloji ve Adli Tıp; Genetik (klinik); Pediatrics, Perinatology and Child Health; Anatomy; Pathology and Forensic Medicine; Genetics (clinical); COL11A2; hearing loss; OSMED; skeletal dysplasia